Multiple-Layer Heat Dissipation Module for LED Streetlamps. - Kang, Shung-Wen (Journal of Applied Science and Engineering)
High powered light emitting diodes (LED) have rapidly developed in recent years from applications in indication devices to wider uses in illumination devices. This study proposed an innovative heat dissipation module for an LED street lamp using a number of substrates positioned in multiple-layer formation. Multi-chip LED arrays were mounted on each substrate. Heat generated by the LEDs was dissipated through a heat dissipation plate formed by the substrates, which connected to heat pipes and a heat sink. This study used several simulation models to determine the natural convection properties of the proposed module. Based on the simulations, a heat dissipation module was manufactured. Module temperatures were measured and compared with simulation results at input powers of 120 and 180 W. Illuminance tests were also conducted to verify the performance of the LED lamp. The multiple-layer substrates were shown to instantly and effectively dissipate heat outward and prevent degradation in the illumination quality of the LED lamp.